Gestational weight gain and eating-related disorders. (17th November 2021) - Zanardo, Vincenzo; Cavaliere, Annafranca; Giliberti, Elia; Giliberti, Lara; Manghina, Valeria; Parotto, Matteo; Severino, Lorenzo; Straface, Gianluca
Abstract: This prospective cohort study took place at the Division of Perinatal Medicine of Policlinico Abano Terme, Italy, from January to November 2018. In the second day postpartum, 463 healthy at term puerperae, 122 (26.35%) with inadequate gestational weight gain (GWG), 210 (45.46%) with adequate GWG, and 131 (28.29%) with excessive GWG, were studied by EAT-26, through distinguishing three factors: 'Dieting', 'Bulimia and food preoccupation', and 'Oral control'. EAT-26 Global score increased from inadequate, to adequate, and excessive GWG puerperae, resulting significantly higher in excessive GWG group ( p = .0029, Anova's). In addition, among EAT-26 subscales 'Dieting' scores significantly increased from inadequate, to adequate, and to excessive GWG category women, resulting significantly higher in excessive GWG group ( p = .006, Anova's). It was found that excessive GWG is a warning indicator of unhealthy eating and 'Dieting' disorders. This relationship highlights the potential for interventions directed towards psychosocial support to have salutary effects upon GWG. Excessive gestational weight gain across an uncomplicated pregnancy is a warning indicator of unhealthy eating and dieting disorders. IMPACT STATEMENT: What is already known on this subject? Pregnancy represents a time of rapid trimester-specific changes in body weight and size. What do the results of this study add? Excessive gestational weight gain is a warning indicator of unhealthy eating and dieting disorders. What are the implications of these findings for clinical practice and/or further research? This relationship highlights the potential for interventions directed towards psychosocial support to have salutary effects upon gestational weight gain.